RELIGION, VIOLENCE ET CRISE DE LÉGITIMITÉ EN RDC. COMPRENDRE LA COMMUNICATION POLITIQUE DES ACTEURS ET LEURS ENJEUX - KADUNDU KARHAMIKIRE, Paul (Studia Universitatis Babes-Bolyai Studia Europaea, 2020)
Religion, Violence and Crisis of Legitimacy in the DRC. Understanding The Political Communication of Actors and their Challenges. This study analyzes the communication of political and religious actors at the end of the regime of J. Kabila. It tries understand why they used religious language. After describing the process of the annihilation of the Congolese opposition, it enlightens the contradictions in the MP communication. It shows how MP was surprised by the popular resistance led by the Lay Coordination Committee (CLC). The discourse of religious actors also diverges despite their concern to safeguard cohesion within the Catholic Church.